Hypernatremia During Intravenous Treatment With Fosfomycin: A Retrospective Medical Record Review Study and an Analysis of Spontaneous Reports in the EudraVigilance Database - Scavone, Cristina; Mascolo, Annamaria; Bernardi, Francesca Futura; Aiezza, Maria Luisa; Saturnino, Paola; Morra, Gaia; Simonelli, Margherita; Massa, Marida; Pomicino, Andrea; Minei, Giuseppina; Pisapia, Raffaella; Spatarella, Micaela; et al. (Frontiers in Pharmacology, 2022)
Background: Hypernatremia is a serious event that can occur during the intravenous (IV) treatment with fosfomycin and it can also be caused by a wrong drug preparation. Considering the clinical significance of hypernatremia, we decided to carry out two studies by using two different data sources with the aim to evaluate cases of IV fosfomycin-induced hypernatremia. Methods: A retrospective medical record review was performed from June 2017 to June 2019 by using data from two hospitals of Southern Italy. The information collected were related to the patients, the antibiotic treatment regimen, type of adverse drug reaction (ADR), hypernatremia’ severity classification and drug’s withdrawal due to ADRs. Moreover, a pharmacovigilance study was performed from the date of European marketing authorization of fosfomycin to October 11th, 2021 by using data reported in the European website of suspected ADRs. Information related to the patient characteristics, treatment, hypernatremia, and reporter were retrieved. Results: From the retrospective medical record review, a total of 62 patients (48 men and 14 women) in treatment with fosfomycin were identified, of which 17 experienced ADRs. Specifically, 11 patients experienced hypernatremia. During the period from June 2017 to June 2018, a total of 63.7% of hypernatremia events were related to the wrong reconstitution of the drug. According to these results a surveillance and training campaign about the correct drug reconstitution was managed. However, from June 2018 to June 2019 we still had 4 new hypernatremia cases. Drug withdrawal occurred in only one patient with hypernatremia. From the pharmacovigilance study, a total of 25 cases of IV fosfomycin-induced hypernatremia were retrieved. No substantial difference was found for patients’ distribution by sex. Most cases were classified as serious (68%) and reported “recovered/resolved” as outcome (44%). In the majority of cases, fosfomycin was the only suspected drug reported (72%). Conclusions: Our results show that training campaign on the correct drug preparation need to be strengthened to allow a reduction of hypernatremia cases. Moreover, when a close monitoring and management is performed by the infectious disease (ID) specialist and the hospital pharmacist, there also is a reduction in the antibiotic withdrawal due to hypernatremia.